Metode Analytical Hierarchy Process dalam Seleksi Peserta Olimpiade Sains Nasional Tingkat SD di SDN Jatimekar IV - Muh. Iqbal Rizky Nurfirdaus; Dwipa Handayani (Journal of Students‘ Research in Computer Science, 2024)
Technological developments that help in the teaching and learning process in the classroom, when selecting OSN participants, each school sends representatives, the same as SDN Jatimekar IV which also sends student representatives from the school. However, there are often difficulties in determining school representatives. So a decision support system (SPK) is needed to determine which students are appointed by school representatives. The research uses the Analytical Hierarchy Process (AHP) algorithm because it has a model that can see the relationship between criteria data and alternative data which helps in determining which students are worthy of representing the school. Therefore, it is hoped that it will help the school to simplify the selection process for students who will be proposed as school representatives. The research results help the selection process for participants in the National Science Olympiad (OSN) at SDN Jatimekar IV.